2019
DOI: 10.1186/s12876-019-0946-8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease patient perceptions of diagnostic and monitoring tests and procedures

Abstract: Background Inflammatory Bowel Disease (IBD) with its high incidence and prevalence rates in Canada generates a heavy burden of tests and procedures. The purpose of this study is to gain a better understanding of the transfer of information from physician to patient, as well as the patient understanding and perceptions about the tests and procedures that are ordered to them in the context of IBD diagnosis and monitoring. Methods An online questionnaire was completed by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
(77 reference statements)
5
20
0
Order By: Relevance
“…The current study found that test explanations by a referring clinician significantly improved parents' levels of understanding when their child had a general blood test, faecal test, US or colonoscopy. Moreover, parents' understanding of the current IBD tests was not influenced by their level of education, similar to the finding in adults with IBD [ 23 ]. Collectively the present findings build upon the parent's role as an integral partner of patient- and family-centred care [ 25 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The current study found that test explanations by a referring clinician significantly improved parents' levels of understanding when their child had a general blood test, faecal test, US or colonoscopy. Moreover, parents' understanding of the current IBD tests was not influenced by their level of education, similar to the finding in adults with IBD [ 23 ]. Collectively the present findings build upon the parent's role as an integral partner of patient- and family-centred care [ 25 ].…”
Section: Discussionsupporting
confidence: 71%
“…The two most ordered tests for children with IBD, as reported by their parents in the current study, are similar to those undertaken by adults with IBD, where general blood tests were the most ordered test by their clinician (97%), followed by colonoscopy (93%) [ 23 24 ]. Furthermore, in the Canadian study, medical imaging (not specified) was the least frequently ordered test (58%) [ 23 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Further information was provided by the authors of two abstracts ( 28 , 29 ). Five studies compared two monitoring tools, two studies compared multiple imaging modalities ( 28 , 30 ) and three studies compared multiple monitoring tools in CD and UC populations ( 29 , 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, the participants had a risk of prior exposure to the outcome. Two studies had inadequate follow-up with 48% and 22.5% response rates ( 30 , 32 ).…”
Section: Resultsmentioning
confidence: 99%